(untitled) (SETARA : Jurnal Ilmu Hukum, 2022)
The crime of rape committed with violence or threats of violence requires careful evidentiary assessment because the judge’s conviction must rest on lawful evidence that is sufficient in quantity and quality. This article examines how judges should assess proof in rape cases and how the demand for justice should guide that assessment, especially in relation to the evidentiary value of visum et repertum and psychiatric examination of victims. Using normative juridical research supported by case analysis, the article reviews the legal framework of rape under the Criminal Code and evaluates Decision Number 42/PID/2017/PT.BJM of the Banjarmasin High Court. The study finds that the decision gave inadequate weight to critical evidence and interpreted violence too narrowly, thereby weakening protection for victims. The article argues that judges should adopt a more progressive and victim-sensitive approach to proof in order to realize substantive justice in sexual violence cases.